Children’s behavior on sugar-sweetened beverages and factors that influence the consumption - Saptawati Bardosono (Indonesian Nutrition Association, 2022)
For Indonesia children, the sugar-sweetened beverages (SSB) drinking behavior is not yet a big problem as compared to other countries, such as Mexico or United States. However, although the soft-drink intake is very minimal, there is a trending higher intake of sweetened milks, sweetened teas dan packaged juice in a daily or weekly bases. Based on age, then the amount and the percentage of SSB consumer age 10–17 years is higher as compared to the younger or older age.